Legal Enforcement Against Non-Compliance by Ex-Husbands with Court Orders on Iddah and Mut’ah Support - Rohayati, Dede; Mohammad Ridwan; Arifin, Tajul; Suhaila Zulkifli; Ramdani Wahyu Sururie; Edy Saputra; Abdulah Pakarti, Muhammad Husni (Nurani: jurnal kajian syari'ah dan masyarakat, 2025)
The failure of a husband to comply with a Religious Court’s ruling on nafkah ‘iddah and mut’ah raises important concerns about the actual enforceability of such decisions, the legal consequences of non-compliance, and the effectiveness of existing mechanisms for enforcing judgments that have attained final and binding legal status. This study aims to scrutinize, from a juridical standpoint, the enforcement mechanisms applied in response to former husbands’ noncompliance with judicial decrees concerning the disbursement of iddah and mut’ah entitlements. This research uses an empirical juridical method with a descriptive qualitative approach because it aims to understand legal phenomena in depth through narrative analysis. The primary dataset comprises insights obtained through interviews with a panel of judges from the Banten High Religious Court, former wives deprived of iddah and mut’ah support, and former husbands who failed to execute court-mandated financial obligations pertaining to said supports. Secondary materials encompass adjudications issued by religious courts, statutory instruments, scholarly volumes, legal periodicals, juridical essays, and expert commentaries. The research findings show that one of the effective law enforcement models is the addition of a clause in the verdict containing property guarantees that can be confiscated if the husband defaults. In addition, the contribution of law enforcement can be realized through the issuance of special regulations that strengthen the execution of decisions. This study highlights the urgent need to strengthen the enforceability of court rulings and to harmonize existing legal frameworks to ensure consistent compliance with post-divorce nafkah and mut’ah obligations.